Solvent Effects on Electronic Circular Dichroism Spectra - Souza, Aguinaldo Robinson de [UNESP]; Ximenes, Valdecir Farias [UNESP]; Morgon, Nelson Henrique; Cheng, H. N.; Maryanoff, C. A.; Miller, B. D.; Schmidt, D. G. (Amer Chemical Soc, 2017)
The Electronic Circular Dichroism Spectrum (ECD) is a valuable tool to study the unknown absolute configuration of an optically active molecule. And the comparison between experimental data and theoretical computational calculations has been a successful strategy for this study. However, the ECD spectrum is very sensitive to solvent effects that significantly change the character of the results obtained. This chapter is focused on the study of the solvent effects and their application in both experimental and computational chemistry of ECD of the compound 3,3'-dibromo- 1,1'-bi-2-naphthol.